Metamorphosis in Motion: A Comparative Analysis of the Identity Changes in First and Final Year BS English Students of IMSciences - Farooq, Shifa; Sabeeb, Dr.; Bhatti, Javeria Ashfaq (The Lighthouse Journal of Social Sciences, 2023)
This study aims to investigate the transformative effects of studying English linguistics and literature on the identities of BS students at IMSciences. The main focus is to critically observe the changes in their identities as they progress from the first to the second year of their academic journey at IMSciences. Data was collected from 33 volunteer participants (selected through purposive sampling) through separate Focus Group Discussions conducted at different stages. The analysis of the study was guided by Vygotsky’s socio-cultural theory and a general Reader-Response theory. The data was categorized into themes and sub-themes for analysis. The findings revealed that the students’ worldviews were altered and their language and communication skills were enhanced during the course of the study. Additionally, the overall social and cultural perceptions of the English language and literature program, as well as the students’ affordability and expectations, played a positive role in shaping their identities.